Malignant Müllerian Mixed Tumor of the Uterine Cervix with a Small Cell Neuroendocrine Carcinoma Component - Satoru Munakata; Emi Iwai; Tomohito Tanaka; Michihiko Nakamura; Takayoshi Kanda (Case Reports in Pathology)
Malignant Müllerian mixed tumors (MMMTs) of the uterine cervix are extremely rare, accounting for 0.005% of all cervical malignancies. To date, only approximately 50 well-documented cases have been reported. Although several epithelial components have been described in cervical MMMTs, small cell neuroendocrine carcinoma (SCC) has not appeared in the English literature. We present a 43-year-old woman, para 2 gravida 2, who had MMMT with SCC and rhabdomyosarcoma components in the uterine cervix. She was referred to our hospital because of a cervical mass with an abnormal Pap smear result. Cervical biopsy revealed SCC. After neoadjuvant chemotherapy with balloon-occluded arterial infusion, she underwent type II radical hysterectomy with pelvic lymphadenectomy. Histological analysis revealed that the cervical tumor comprised SCC and rhabdomyosarcoma components. Genotype analysis indicated human papillomavirus type 18. She underwent concurrent chemoradiation therapy. The patient had been free of the disease and showed no evidence of recurrence 38 months after operation.